Follow-Up of Thyroid Function in Children With Neonatal Hyperthyroidism - Pyrżak, Beata; Rumińska, Małgorzata; Witkowska-Sędek, Ewelina; Kucharska, Anna (Frontiers in Endocrinology, 2022)
Introduction: Neonatal hyperthyroidism mainly occurring in the children born to mothers with Graves’ disease (GD). The influence of maternal GD on the newborn's thyroid function includes not only hyperthyroidism, but also various forms of hypothyroidism. Maternally transferred thyrotropin receptor antibodies (TRAb), the antithyroid drug (ATD) administration during pregnancy and previous definitive treatment of GD (radioactive iodine therapy or thyroidectomy) in the mother impact the function of the fetal/neonatal thyroid. Some newborns born to mothers with GD may present central hypothyroidism (CeH) due to impaired regulation of the fetal hypothalamic-pituitary-thyroid axis. The aim of this study was to evaluate different types of thyroid dysfunction in babies with neonatal hyperthyroidism. Materials and methods: Medical records of 14 infants with neonatal hyperthyroidism (13 born to mothers with GD, and one born to mother with Hashimoto thyroiditis) were analyzed. Results: Transient hyperthyroidism was the main thyroid dysfunction in our study group. Overt hyperthyroidism with highly increased TRAb levels (mean 13.0 ± 7.0 IU/L) was diagnosed in 6 (43%) neonates. Another 6 (43%) babies presented hyperthyroidism with slightly increased fT4 and/or fT3 levels and TSH levels in the lower limit of the normal range coinciding with positive TRAb levels (mean 3.8 ± 1.6 IU/L). Normal thyroid hormone levels with TSH levels below the lower limit of the range were observed in 2 (14%) neonates. Four babies in the study group (28.5%) required further levothyroxine (L-T4) supplementation due to CeH or, in one case, due to primary hypothyroidism. Conclusions: Our study highlights the need for prolonged monitoring of thyroid function in children born to mothers with GD. Diagnosis of CeH could be delayed due to its masking by transient hyperthyroidism. Prolonged thyroid-stimulating hormone suppression after TRAb elimination should be considered as a signal announcing CeH. I